(untitled) (Palimpsesto, 2017)
The present paper aims to demostrate that the outcome of the peace negotiations that advanced in Havana, between the Colombian government and the Revolutionary Armed Forces of Colombia People’s Army (FARC-EP), does not significantly alter the security situation Present in the Colombian Caribbean. This is because the armed insurgency represented by the Bloque Caribe or Martín Caballero of the FARC EP and the Northern War Front of the National Liberation Army (ELN) was strategically defeated in this region of Colombia between 2004 and 2009. Giving way to new forms of criminal violence. Â